Lithium ion battery positive electrode material precursor and preparation method thereof, lithium ion battery positive electrode material, lithium ion battery and electrical equipment

By using the lithium-ion battery positive electrode material precursor formed by primary particles composed of neatly stacked monolithic layers, the performance decay caused by phase change during charging and discharging of high-nickel positive electrode materials is solved, and a higher cycling performance and capacity retention rate is achieved.

CN116425219BActive Publication Date: 2025-04-08CNGR ADVANCED MATERIAL CO LTD +1

Patent Information

Application Number
CN202310429383.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-20
Publication Date
2025-04-08
Estimated Expiration
2043-04-20

AI Technical Summary

Technical Problem

The anisotropic stress caused by phase change during charging and discharging of high-nickel positive electrode materials triggers cracks and side reactions, resulting in severe decline in battery performance.

Method used

The lithium-ion battery positive electrode material precursor formed by primary particles composed of neatly stacked monolithic layers ensures that the edges of the monolithic layer are flat, and the regularity and integrity of the primary particles are improved, thereby reducing crystal defects and side reactions.

Benefits of technology

By increasing the crystallinity and regularity of the positive electrode material, reducing side reactions, the circulation performance and capacity retention rate of lithium-ion batteries are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116425219B_ABST
    Figure CN116425219B_ABST
Patent Text Reader

Abstract

The present application provides a lithium-ion battery positive electrode material precursor and a preparation method thereof, a lithium-ion battery positive electrode material, a lithium-ion battery and electrical equipment, and relates to the field of lithium-ion batteries. A lithium-ion battery positive electrode material precursor, wherein the precursor comprises a plurality of primary particles, and a primary particle comprises a plurality of neatly stacked monolayers, and the edges of the monolayers are flat. The preparation method comprises: passing raw materials including a nickel-containing metal salt solution, a precipitant, and a complexing agent into a bottom liquid for reaction, and controlling the pH to be 9.8-11.3, the ammonia concentration to be 2-12 g / L, and the nickel concentration in the supernatant to be 70-350 ppm during the reaction; after the reaction, solid-liquid separation, drying, and sieving and demagnetization are performed to obtain a lithium-ion battery positive electrode material precursor. In the lithium-ion battery positive electrode material precursor, the plurality of monolayers constituting the primary particles have the characteristics of high regularity and integrity, and the prepared positive electrode material has higher circulation, capacity and safety.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of lithium-ion batteries, and in particular to a lithium-ion battery positive electrode material precursor and a preparation method thereof, a lithium-ion battery positive electrode material, a lithium-ion battery and electrical equipment. Background Art

[0002] With the development of energy storage technology, the threshold requirements and cost requirements for energy density per unit volume of lithium battery materials are rapidly increasing. Against this background, positive electrode materials are gradually developing towards high nickel. Although high nickel positive electrode materials have advantages in cost and capacity, high nickel materials also have poor cycle performance and are accompanied by serious performance degradation.

[0003] Studies have shown that the phase change of high-nickel positive electrode materials during the charging and discharging process will cause changes in the volume of the positive electrode material crystals, generating anisotropic stress, which can easily cause primary cracks within and between crystals and trigger a vicious cycle of diffuse cracks, triggering more side reactions, and finally causing the entire positive electrode material structure to collapse and break, causing serious degradation of battery performance.

[0004] The cathode material precursor is a highly customized standard product of cathode materials and is a key material for the production of cathode materials. The characteristics of the precursor directly determine the main physical and chemical properties of the cathode material, such as particle size, particle size distribution, ratio of metal elements other than lithium, and impurity content, thus affecting the core electrochemical properties of lithium batteries, such as rate performance, energy density, and cycle life.

[0005] Currently, most high-nickel precursors on the market are secondary particles agglomerated from primary particles with a wide length and width distribution range. Because of the wide length and width distribution range of these secondary particles, it is easy to see that the primary particles are uneven in morphology in the electron microscope image of the secondary particles after Li-doped sintering into positive electrode materials. Although they can have a very high capacity due to the advantage of high nickel element ratio, the primary particles of the material itself are uneven, the crystallinity is poor, and there are many crystal defects. Although the sintered positive electrode material has a high capacity, its cycle capacity is poor, which restricts the full application of high-nickel materials in lithium-ion batteries. Summary of the invention

[0006] The purpose of the present application is to provide a lithium-ion battery positive electrode material precursor and a preparation method thereof, a lithium-ion battery positive electrode material, a lithium-ion battery and electrical equipment to solve the above-mentioned problems.

[0007] To achieve the above objectives, this application adopts the following technical solutions:

[0008] A lithium-ion battery positive electrode material precursor, wherein one precursor secondary particle includes N primary particles, and one primary particle includes N neatly stacked single sheets, and the edges of the single sheets are flat;

[0009] Wherein, N is a positive integer and N≥2.

[0010] Preferably, in a precursor secondary particle, at least 60% of the primary particles meet requirement ①: the primary particle length is not less than 200 nm, the primary particle width is not less than 50 nm, and the primary particle aspect ratio is not less than 1.2;

[0011] Preferably, in a precursor secondary particle, at least 70% of the primary particles meet requirement ②: the primary particle length is 200-3000nm, the primary particle width is 50-300nm, and the primary particle aspect ratio is not less than 1.2.

[0012] The length, width and aspect ratio of the primary particles of the precursor must be within a certain range. If the width is too narrow and the length is too short, the corresponding internal pores of the precursor will be very small, and the positive electrode material after sintering will not be able to inherit the internal pores, resulting in a low porosity of the positive electrode material, which will cause the ion transmission path to be too long, thus affecting the electrochemical performance.

[0013] Preferably, in one precursor secondary particle, at least 20% of the primary particles meet requirement ③:

[0014] The monolayer includes a broken monolayer and / or an unbroken monolayer, and the broken monolayer is in a straight line or a bent shape;

[0015] When the broken single layer is bent, the minimum angle γ between the extension line of the straight portion and the bent portion is less than or equal to 30°.

[0016] Preferably, in one precursor secondary particle, at least 20% of the primary particles meet at least one of the following requirements:

[0017] Requirement ④: In a primary particle, the monolayer includes broken monolayers and / or unbroken monolayers, and the number of fractures of each broken monolayer is less than or equal to 2;

[0018] Requirement ⑤: In a primary particle, the monolithic layer includes broken monolithic layers and / or unbroken monolithic layers, and the length of the longest fragment in each broken monolithic layer accounts for no less than 50% of the total length of the monolithic layer in which it is located;

[0019] Requirement ⑥: In a primary particle, the monolayer includes broken monolayers and / or unbroken monolayers, and the sum of the total length of all unbroken monolayers and the total length of the longest fragments of all broken monolayers accounts for no less than 60% of the total length of all monolayers.

[0020] Preferably, the lithium-ion battery cathode material precursor satisfies at least one of the following conditions:

[0021] A. Precursor particle size D50 is 4-20μm;

[0022] B. The half-peak width FWHM(001) of the (001) crystal plane corresponding to the diffraction angle 2θ=19.2±1° and the half-peak width FWHM(101) of the (101) crystal plane corresponding to the diffraction angle 2θ=38.5±1° of the precursor are both less than 0.550°;

[0023] C. The BET surface area of ​​the precursor is 3-20m 2 / g;

[0024] D. The precursor chemical formula is Ni x M 1-x (OH)2, wherein 0.6≤x<1, and M is at least one of Co, Mn, Al, Fe, Ti, Zr, Mo, Cr, W, B, Mg, Ba, Nb and Sr;

[0025] E. The precursor chemical formula is Ni x Co y Mn z M 1 1-x-y-z (OH)2, where 0.6≤x<1, 0≤y≤0.4, 0≤z≤0.4, 1-xy≥0; M 1 It is at least one of Al, Fe, Ti, Zr, Mo, Cr, W, B, Mg, Ba, Nb and Sr.

[0026] The present application also provides a method for preparing a lithium-ion battery positive electrode material precursor, comprising:

[0027] The raw materials including nickel metal salt solution, precipitant and complexing agent are introduced into the bottom liquid for reaction. During the reaction, the pH is controlled at 9.8-11.3, the ammonia concentration is 2-12 g / L, and the nickel concentration in the supernatant is 70-350 ppm. After the reaction, the precursor of the positive electrode material of lithium ion battery is obtained by solid-liquid separation, drying, sieving and demagnetization.

[0028] The above preparation method satisfies at least one of the following conditions:

[0029] a. The nickel-containing metal salt solution contains nickel metal, which is at least one of Ni, Co and Mn;

[0030] b. The nickel-containing metal salt solution contains only Ni;

[0031] c. The raw material introduced into the bottom solution further includes a doped metal salt solution, and the doped metal in the doped metal salt solution includes at least one of Al, Fe, Ti, Zr, Mo, Cr, W, B, Mg, Ba, Nb and Sr;

[0032] d. The precipitating agent includes sodium hydroxide solution, and the complexing agent includes aqueous ammonia;

[0033] e. The flow rate of the nickel metal salt solution is 2-10% / h of the available volume of the reactor, the flow rate of the precipitant is 0.5-3.5% / h of the available volume of the reactor, and the flow rate of the complexing agent is 0.01-1% / h of the available volume of the reactor;

[0034] f. The base liquid includes sodium hydroxide solution, ammonia water and water;

[0035] g. The pH of the base solution is 10.5-12.3, and the ammonia concentration of the base solution is 3.4-6g / L;

[0036] h. The mother liquor is discharged during the reaction. The total liquid inlet rate is the sum of the raw material flow rates simultaneously introduced into the bottom liquid. The mother liquor discharge rate is consistent with the total liquid inlet rate.

[0037] The present application also provides a lithium-ion battery positive electrode material, the raw materials of which include a lithium-ion battery positive electrode material precursor.

[0038] The present application also provides a lithium-ion battery, including a lithium-ion battery positive electrode material.

[0039] The present application also provides an electrical device, including a lithium-ion battery.

[0040] Compared with the prior art, the beneficial effects of this application include:

[0041] The lithium-ion battery positive electrode material precursor provided by the present application is composed of primary particles, and one primary particle includes multiple neatly stacked single-layers with smooth edges of the single-layers; the multiple single-layers constituting the primary particles have the characteristics of high regularity and high integrity, which means that the half-peak width on the (001) crystal plane and the (101) crystal plane is narrow, with high crystallinity and fewer crystal defects, which can effectively reduce side reactions during battery use, inhibit damage to the secondary particle structure during repeated charge and discharge, and improve the capacity retention rate after cycling.

[0042] The regularity of the monolayer refers to the fact that the shapes and sizes of the multiple monolayers in a primary particle are relatively consistent, their edges are flat and they are neatly stacked. High monolayer integrity means that there are few broken monolayers in the same primary particle, the number of broken monolayers is small, and the proportion of long fragments is large; the bending deformation of the broken monolayer is small, and the minimum angle γ between the extension line of the straight part and the bending part is small.

[0043] The method for preparing a precursor of a positive electrode material for a lithium-ion battery provided in the present application obtains precursor secondary particles formed by the above-mentioned primary particles including a plurality of monolayers by controlling the pH, ammonia concentration and nickel content of the supernatant during the reaction. The process is simple and the product quality stability between batches is good.

[0044] The lithium-ion battery positive electrode material provided in the present application has higher capacity and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0046] Figure 1 Schematic diagram of a primary particle and a single layer constituting the primary particle;

[0047] Figure 2 It is a schematic diagram of the length and width of a primary particle;

[0048] Figure 3 Schematic diagram of the minimum angle γ between the extension line of the straight part of the broken single layer and the bent part in requirement ③;

[0049] Figure 4 Schematic diagram of a fractured monolithic layer that meets requirement ⑤;

[0050] Figure 5 Schematic diagram of a broken monolithic layer that does not meet requirement ⑤;

[0051] Figure 6 Schematic diagram of N broken monolithic layers in a primary particle meeting requirement ⑥;

[0052] Figure 7 Schematic diagram of multiple broken monolithic layers in a primary particle that does not meet requirement ⑥;

[0053] Figure 8 The lithium ion battery ternary positive electrode material precursor Ni obtained in Example 1 0.95 Co 0.04 Mn 0.01 Local SEM image of (OH)2 secondary particles;

[0054] Fig. 9 The lithium ion battery ternary positive electrode material precursor Ni obtained in Example 1 0.95 Co 0.04 Mn 0.01 XRD spectrum of (OH)2;

[0055] Fig.10 The lithium ion battery ternary positive electrode material precursor Ni obtained in Example 2 0.95 Co 0.04 Mn 0.01 Local SEM image of (OH)2 secondary particles;

[0056] Fig.11 The lithium ion battery ternary positive electrode material precursor Ni obtained in Example 2 0.95 Co0.04 Mn 0.01 XRD spectrum of (OH)2;

[0057] Fig.12 The lithium ion battery ternary positive electrode material precursor Ni obtained in Example 3 0.95 Co 0.04 Mn 0.01 Local SEM image of (OH)2 secondary particles;

[0058] Fig.13 The lithium ion battery ternary positive electrode material precursor Ni obtained in Example 3 0.95 Co 0.04 Mn 0.01 XRD spectrum of (OH)2;

[0059] Fig.14 The lithium ion battery ternary positive electrode material precursor Ni obtained in Comparative Example 1 0.95 Co 0.04 Mn 0.01 Local SEM image of (OH)2 secondary particles;

[0060] Fig.15 The lithium ion battery ternary positive electrode material precursor Ni obtained in Comparative Example 1 0.95 Co 0.04 Mn 0.01 XRD spectrum of (OH)2;

[0061] Fig.16 The lithium ion battery ternary positive electrode material precursor Ni obtained in Comparative Example 2 0.95 Co 0.04 Mn 0.01 Local SEM image of (OH)2 secondary particles;

[0062] Fig.17 The lithium ion battery ternary positive electrode material precursor Ni obtained in Comparative Example 2 0.95 Co 0.04 Mn 0.01 XRD spectrum of (OH)2. DETAILED DESCRIPTION

[0063] As used herein:

[0064] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0065] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0066] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range.

[0067] In these examples, parts and percentages are by mass unless otherwise indicated.

[0068] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.

[0069] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0070] A lithium-ion battery positive electrode material precursor, the precursor is composed of primary particles, one primary particle includes a plurality of neatly stacked single-sheet layers, and the edges of the single-sheet layers are flat.

[0071] Schematic diagram of primary particles and the single layer that makes up the primary particles is shown in Figure 1 It should be noted that each primary particle is formed by stacking N sheets of monolayers, where N is a positive integer and N≥2. The "smooth edge" referred to in this application means that the edge of the monolayer is smooth without obvious concave and convex shapes.

[0072] The "neatly stacked" referred to here means that each single layer is stacked together in a parallel or substantially parallel state, and each single layer does not undergo a large displacement along one edge of the stacking direction (width direction), similar to the stacking state of pages in a closed book.

[0073] In an optional embodiment, in a precursor secondary particle, at least 60% of the primary particles meet requirement ①: the primary particle length is not less than 200 nm, the primary particle width is not less than 50 nm, and the primary particle aspect ratio is not less than 1.2;

[0074] In an optional embodiment, in a precursor secondary particle, at least 70% of the primary particles meet requirement ②: the primary particle length is 200-3000nm, the primary particle width is 50-300nm, and the primary particle aspect ratio is not less than 1.2.

[0075] The schematic diagram of the width and length of a primary particle is as follows Figure 2 As shown, that is, the width direction is along the stacking direction of the single layers, and the length direction is along the extending direction of the single layers.

[0076] In an optional embodiment, in a precursor secondary particle, at least 20% of the primary particles meet requirement ③:

[0077] The monolayer includes a broken monolayer and / or an unbroken monolayer, and the broken monolayer is in a straight line or a bent shape;

[0078] When the broken single layer is bent, the minimum angle γ between the extension line of the straight portion and the bent portion is less than or equal to 30°.

[0079] like Figure 3 As shown, the minimum angle γ between the extension line of the straight part of the broken single layer in ③ and the bent part is required to be ≤30°.

[0080] In an optional embodiment, in a precursor secondary particle, at least 20% of the primary particles meet at least one of the following requirements:

[0081] Requirement ④: In a primary particle, the monolayer includes broken monolayers and / or unbroken monolayers, and the number of fractures of each broken monolayer is less than or equal to 2;

[0082] Requirement ⑤: In one of the primary particles, the monolithic layers include broken monolithic layers and / or unbroken monolithic layers, and the length of the longest fragment in each broken monolithic layer accounts for no less than 50% of the total length of the monolithic layer in which it is located;

[0083] For example, Figure 4 and Figure 5 As shown, Figure 4Schematic diagram of a fractured monolithic layer that meets requirement ⑤. Figure 5 Schematic diagram of a broken single layer that does not meet requirement ⑤.

[0084] Requirement ⑥: In a primary particle, the monolayer includes broken monolayers and / or unbroken monolayers, and the sum of the total length of all unbroken monolayers and the total length of the longest fragments of all broken monolayers accounts for no less than 60% of the total length of all monolayers.

[0085] For example, Figure 6 and 7 As shown, assuming that all the monolayers in the same primary particle have the same length and the fracture positions in the fractured monolayers are consistent, Figure 6 The total length of the longest fragment of all the broken monolayers shown in the figure accounts for 70% of the total length of all the monolayers in the primary particle where it is located, which meets the requirement ⑥;

[0086] Figure 7 The total length of the longest fragment of all the broken monolayers shown in the figure accounts for 59.4% of the total length of all the monolayers in the primary particle where it is located, which does not meet the requirement ⑥.

[0087] In an optional embodiment, the lithium-ion battery positive electrode material precursor satisfies at least one of the following conditions:

[0088] A. Precursor particle size D50 is 4-20μm;

[0089] B. The half-peak width FWHM(001) of the (001) crystal plane corresponding to the diffraction angle 2θ=19.2±1° and the half-peak width FWHM(101) of the (101) crystal plane corresponding to the diffraction angle 2θ=38.5±1° of the precursor are both less than 0.550°;

[0090] C. The BET surface area of ​​the precursor is 3-20m 2 / g;

[0091] D. The precursor chemical formula is Ni x M 1-x (OH)2, wherein 0.6≤x<1, and M is at least one of Co, Mn, Al, Fe, Ti, Zr, Mo, Cr, W, B, Mg, Ba, Nb and Sr;

[0092] E. Its chemical formula is Ni x Co y Mn z M 1 1-x-y-z (OH)2, where 0.6≤x<1, 0≤y≤0.4, 0≤z≤0.4, 1-xy≥0; M 1It is at least one of Al, Fe, Ti, Zr, Mo, Cr, W, B, Mg, Ba, Nb and Sr.

[0093] The present application also provides a method for preparing a lithium-ion battery positive electrode material precursor, comprising:

[0094] The raw materials including nickel metal salt solution, precipitant and complexing agent are introduced into the bottom liquid for reaction. During the reaction, the pH is controlled at 9.8-11.3, the ammonia concentration is 2-12 g / L, and the nickel concentration in the supernatant is 70-350 ppm. After the reaction, the precursor of the positive electrode material of lithium ion battery is obtained by solid-liquid separation, drying, sieving and demagnetization.

[0095] In an optional embodiment, the above preparation method satisfies at least one of the following conditions:

[0096] a. The nickel-containing metal salt solution contains nickel metal, which is at least one of Ni, Co and Mn;

[0097] b. The nickel-containing metal salt solution contains only Ni;

[0098] c. The raw material introduced into the bottom solution further includes a doped metal salt solution, and the doped metal in the doped metal salt solution includes at least one of Al, Fe, Ti, Zr, Mo, Cr, W, B, Mg, Ba, Nb and Sr;

[0099] It should be noted that the doping metal salt can be prepared together with the nickel-containing metal salt to form a mixed solution for use, or it can be prepared separately into a doping metal salt solution and then flowed into the reactor together with the nickel-containing metal salt solution. The expression of this application here should not be understood as "the doping metal salt must be prepared separately from the nickel-containing metal salt for use".

[0100] d. The precipitating agent includes sodium hydroxide solution, and the complexing agent includes aqueous ammonia;

[0101] e. The flow rate of the nickel metal salt solution is 2-10% / h of the available volume of the reactor, the flow rate of the precipitant is 0.5-3.5% / h of the available volume of the reactor, and the flow rate of the complexing agent is 0.01-1% / h of the available volume of the reactor;

[0102] Optionally, the flow rate of the nickel-containing metal salt solution can be 2% / h, 3% / h, 4% / h, 5% / h, 6% / h, 7% / h, 8% / h, 9% / h, 10% / h or any value between 2-10% / h of the available volume of the reactor, and the flow rate of the precipitant can be 0.5% / h, 1.0% / h, 1.5% / h, 2.0% / h, 2.5% / h, 3.0% / h, 3.5% / h. The flow rate of the complexing agent can be 0.01% / h, 0.05% / h, 0.1% / h, 0.2% / h, 0.3% / h, 0.4% / h, 0.5% / h, 0.6% / h, 0.7% / h, 0.8% / h, 0.9% / h, 1% / h of the available volume of the reactor or any value between 0.01-1% / h;

[0103] f. The base liquid includes sodium hydroxide solution, ammonia water and water;

[0104] g. The pH of the base solution is 10.5-12.3, and the ammonia concentration of the base solution is 3.4-6g / L;

[0105] Optionally, the pH of the base solution may be 10.5, 10.6, 10.7, 10.8, 10.9, 11.0, 11.1, 11.2, 11.3, 11.4, 11.5, 11.6, 11.7, 11.8, 11.9, 12.0, 12.1, 12.1, 12.2, 12.3 or any value between 10.5 and 12.3, and the ammonia concentration of the base solution may be 3.4 g / L, 3.5 g / L, 3.6 g / L, 3.7 g / L, 3.8 g / L, 3.9 g / L, 4.0 g / L, 4.5 g / L, 5 g / L, 5.5 g / L, 6.0 g / L or any value between 3.4 and 6 g / L;

[0106] h. During the reaction, the mother liquor is discharged. The total liquid inlet rate is the sum of the raw material flow rates simultaneously introduced into the bottom liquid. The mother liquor discharge rate is consistent with the total liquid inlet rate.

[0107] The present application also provides a lithium-ion battery positive electrode material, the raw materials of which include a lithium-ion battery positive electrode material precursor.

[0108] The present application also provides a lithium-ion battery, including a lithium-ion battery positive electrode material.

[0109] The present application also provides an electrical device, including a lithium-ion battery.

[0110] The electrical equipment referred to in this application includes equipment that directly or indirectly uses lithium-ion batteries, such as electric vehicles, electric bicycles, mobile phones, tablet computers, power banks, energy storage stations, etc.

[0111] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0112] First of all, it should be noted that primary particles with high regularity and integrity represent that the material has high crystallinity, and the corresponding XRD half-peak width is significantly narrower than that of similar products. At the same time, when the cross-sectional structure has the same porosity, it has a lower BET, indicating that its crystal defects are reduced, reducing side reactions during circulation.

[0113] Example 1 (ternary precursor: Ni 0.95 Co 0.04 Mn 0.01 (OH)2)

[0114] This embodiment provides a lithium ion battery positive electrode material precursor, and the preparation method thereof is as follows:

[0115] Step 1: Solution preparation

[0116] According to the metal molar ratio of nickel, cobalt and manganese of 95:4:1, nickel sulfate, cobalt sulfate and manganese sulfate crystals were weighed and calculated to prepare a nickel-containing metal salt solution with a total metal content of 2 mol / L.

[0117] Step 2: Primer Preparation

[0118] Pure water, NaOH solution (concentration 32wt%), and ammonia water (concentration 21wt%) were added into the reaction kettle, and stirred evenly at a constant temperature of 65°C to obtain a base solution with a pH of 11.75 and an ammonia concentration of 4g / L;

[0119] Step 3: Material preparation

[0120] Under stirring, constant temperature of 65° C. and nitrogen protection, a nickel-containing metal salt solution (flow rate: 4% / h of the available volume of the reactor), a NaOH solution (flow rate: 1.4% / h to 1.5% / h of the available volume of the reactor) and ammonia water (flow rate: 0.08% / h to 0.16% / h of the available volume of the reactor) are simultaneously introduced into the reactor containing the bottom liquid; during the reaction process, the mother liquor is discharged through the concentration equipment, and the discharge rate of the mother liquor is consistent with the total liquid inlet rate;

[0121] During the reaction, the pH was adjusted to 10.4-10.7 within 4 hours of feeding by fine-tuning the flow rate of NaOH solution and ammonia water, and the ammonia concentration fluctuated within the range of 3-7 g / L, and the nickel concentration in the supernatant was changed and maintained within the range of 170-230 ppm, and finally a metal hydroxide reaction precipitate slurry with a diameter D50 of 14 μm was obtained. After washing, centrifuging, drying, and sieving to remove magnetism, the reaction precipitate slurry was obtained as a precursor of the lithium-ion battery ternary positive electrode material Ni 0.95 Co 0.04 Mn 0.01 (OH)2.

[0122] The obtained lithium-ion battery ternary cathode material precursor Ni 0.95 Co 0.04 Mn 0.01 The local SEM photo of the secondary particles of (OH)2 is as follows Figure 8 Its XRD spectrum is shown in Fig. 9 shown.

[0123] Example 2 (ternary precursor: Ni 0.95 Co 0.04 Mn 0.01 (OH)2)

[0124] This embodiment provides a lithium ion battery positive electrode material precursor, and the preparation method thereof is as follows:

[0125] Step 1: Solution preparation

[0126] According to the metal molar ratio of nickel, cobalt and manganese of 95:4:1, nickel sulfate, cobalt sulfate and manganese sulfate crystals were weighed and calculated to prepare a nickel-containing metal salt solution with a total metal content of 2 mol / L.

[0127] Step 2: Primer Preparation

[0128] Pure water, NaOH solution (concentration 32wt%), and ammonia water (concentration 21wt%) were added into the reaction kettle, and stirred evenly at a constant temperature of 60°C to obtain a base solution with a pH of 11.85 and an ammonia concentration within the range of 5g / L;

[0129] Step 3: Material preparation

[0130] Under stirring, constant temperature of 60° C. and nitrogen protection, a nickel-containing metal salt solution (flow rate: 4% of the available volume of the reactor), a NaOH solution (flow rate: 1.4% / h to 1.5% / h of the available volume of the reactor) and an ammonia solution (flow rate: 0.08% / h to 0.16% / h of the available volume of the reactor) are simultaneously introduced into a reactor containing a bottom liquid; during the reaction process, the mother liquor is discharged through a concentration device, and the discharge rate of the mother liquor is consistent with the total liquid inlet rate;

[0131] During the reaction, by fine-tuning the flow rate of NaOH solution and ammonia water, the pH was adjusted to the range of 10.20-10.70 within 4 hours of feeding, and the ammonia concentration fluctuated within the range of 3-7 g / L. The nickel concentration in the supernatant was changed and maintained within the range of 250-330 ppm, and finally a metal hydroxide reaction precipitation slurry with a diameter D50 of 14 μm was obtained.

[0132] The reaction precipitate slurry is washed, centrifuged, dried, sieved and demagnetized to obtain the precursor Ni for the ternary positive electrode material of lithium-ion battery. 0.95 Co 0.04 Mn 0.01 (OH)2.

[0133] The obtained lithium-ion battery ternary cathode material precursor Ni 0.95 Co 0.04 Mn 0.01 The local SEM photo of the secondary particles of (OH)2 is as follows Fig.10 Its XRD spectrum is shown in Fig.11 shown.

[0134] Example 3 (ternary precursor: Ni 0.95 Co 0.04 Mn 0.01 (OH)2)

[0135] This embodiment provides a lithium ion battery positive electrode material precursor, and the preparation method thereof is as follows:

[0136] Step 1: Solution preparation

[0137] According to the metal molar ratio of nickel, cobalt and manganese of 95:4:1, nickel sulfate, cobalt sulfate and manganese sulfate crystals were weighed and calculated to prepare a nickel-containing metal salt solution with a total metal content of 2 mol / L.

[0138] Step 2: Primer Preparation

[0139] Pure water, NaOH solution (concentration 32wt%), and ammonia water (concentration 21wt%) were added into the reaction kettle, and stirred evenly at a constant temperature of 55°C to obtain a base solution with a pH of 11.60 and an ammonia concentration of 6g / L;

[0140] Step 3: Material preparation

[0141] Under stirring, constant temperature of 55° C. and nitrogen protection, a nickel-containing metal salt solution (flow rate: 4% / h of the available volume of the reactor), a NaOH solution (flow rate: 1.4% / h to 1.5% / h of the available volume of the reactor) and ammonia water (flow rate: 0.08% / h to 0.16% / h of the available volume of the reactor) are simultaneously introduced into a reactor containing a bottom liquid; during the reaction process, the mother liquor is discharged through a concentration device, and the discharge rate of the mother liquor is consistent with the total liquid inlet rate;

[0142] During the reaction, the pH was adjusted to 11.00-11.20 within 4 hours of feeding by fine-tuning the flow rate of NaOH solution and ammonia water, and the ammonia concentration fluctuated within the range of 3-7 g / L, and the nickel concentration in the supernatant was changed and maintained within the range of 80-150 ppm, and finally a metal hydroxide reaction precipitation slurry with a diameter D50 of 14 μm was obtained. After washing, centrifuging, drying, and sieving to remove magnetism, the reaction precipitation slurry was obtained as a precursor of the lithium-ion battery ternary positive electrode material Ni 0.95 Co 0.04 Mn 0.01 (OH)2.

[0143] The obtained lithium-ion battery ternary cathode material precursor Ni 0.95 Co 0.04 Mn 0.01 The local SEM photo of the secondary particles of (OH)2 is as follows Fig.12 Its XRD spectrum is shown in Fig.13 shown.

[0144] Example 4 (binary precursor: Ni 0.95 Mn 0.05 (OH)2)

[0145] This embodiment provides a lithium ion battery positive electrode material precursor, and the preparation method thereof is as follows:

[0146] Step 1: Solution preparation

[0147] According to the metal molar ratio of nickel to manganese of 95:5, nickel sulfate and manganese sulfate crystals were weighed and calculated to prepare a nickel-containing metal salt solution with a total metal content of 2 mol / L.

[0148] Step 2: Primer Preparation

[0149] Pure water, NaOH solution (concentration 32wt%), and ammonia water (concentration 21wt%) were added into the reaction kettle, and stirred evenly at a constant temperature of 60°C to obtain a base solution with a pH of 11.90 and an ammonia concentration of 6g / L;

[0150] Step 3: Material preparation

[0151] Under stirring, constant temperature of 60° C. and nitrogen protection, a nickel-containing metal salt solution (flow rate: 4% / h of the available volume of the reactor), a NaOH solution (flow rate: 1.4% / h to 1.5% / h of the available volume of the reactor) and ammonia water (flow rate: 0.08% / h to 0.16% / h of the available volume of the reactor) are simultaneously introduced into the reactor containing the bottom liquid; during the reaction process, the mother liquor is discharged through the concentration equipment, and the discharge rate of the mother liquor is consistent with the total liquid inlet rate;

[0152] During the reaction, the pH was adjusted to 11.00-11.20 within 4 hours of feeding by fine-tuning the flow rate of NaOH solution and ammonia water, and the ammonia concentration fluctuated within the range of 3-7 g / L, and the nickel concentration in the supernatant was changed and maintained within the range of 80-150 ppm, and finally a metal hydroxide reaction precipitation slurry with a diameter D50 of 14 μm was obtained. After washing, centrifuging, drying, and sieving to remove magnetism, the reaction precipitation slurry was obtained as a precursor of the lithium-ion battery ternary positive electrode material Ni 0.95 Mn 0.05 (OH)2.

[0153] Example 5 (ternary precursor: Ni 0.7 Co 0.1 Mn 0.2 (OH)2)

[0154] This embodiment provides a lithium ion battery positive electrode material precursor, and the preparation method thereof is as follows:

[0155] Step 1: Solution preparation

[0156] According to the metal molar ratio of nickel, cobalt and manganese of 70:10:20, nickel sulfate, cobalt sulfate and manganese sulfate crystals were weighed and calculated to prepare a nickel-containing metal salt solution with a total metal content of 2 mol / L.

[0157] Step 2: Primer Preparation

[0158] Pure water, NaOH solution (concentration 32wt%), and ammonia water (concentration 21wt%) were added into the reaction kettle, and stirred evenly at a constant temperature of 50°C to obtain a base solution with a pH of 11.40 and an ammonia concentration of 3.4g / L;

[0159] Step 3: Material preparation

[0160] Under stirring, constant temperature of 50° C. and nitrogen protection, a nickel-containing metal salt solution (flow rate: 4% / h of the available volume of the reactor), a NaOH solution (flow rate: 1.4% / h-1.5% / h of the available volume of the reactor) and ammonia water (flow rate: 0.08% / h-0.16% / h of the available volume of the reactor) are simultaneously introduced into the reactor containing the bottom liquid; during the reaction process, the mother liquor is discharged through the concentration equipment, and the discharge rate of the mother liquor is consistent with the total liquid inlet rate;

[0161] During the reaction, the pH was adjusted to 11.00-11.20 within 4 hours of feeding by fine-tuning the flow rate of NaOH solution and ammonia water, and the ammonia concentration fluctuated within the range of 3-7 g / L, and the nickel concentration in the supernatant was changed and maintained within the range of 70-100 ppm, and finally a metal hydroxide reaction precipitation slurry with a diameter D50 of 10 μm was obtained. After washing, centrifuging, drying, and sieving to remove magnetism, the reaction precipitation slurry was obtained as a precursor of the lithium-ion battery ternary positive electrode material Ni 0.7 Co 0.1 Mn 0.2 (OH)2.

[0162] Example 6 (Quaternary Precursor: Ni 0.95 Co 0.03 Mn 0.015 Al 0.005 (OH)2:)

[0163] This embodiment provides a lithium ion battery positive electrode material precursor, and the preparation method thereof is as follows:

[0164] Step 1: Solution preparation

[0165] According to the molar ratio of nickel, cobalt, manganese and aluminum of 95:3:1.5:0.5, nickel sulfate, cobalt sulfate, manganese sulfate and aluminum sulfate crystals are weighed and calculated to prepare a nickel-containing metal salt solution with a total metal content of 2 mol / L.

[0166] Step 2: Primer Preparation

[0167] Pure water, NaOH solution (concentration 32wt%), and ammonia water (concentration 21wt%) were added into the reaction kettle, and stirred evenly at a constant temperature of 65°C to obtain a base solution with a pH of 11.40 and an ammonia concentration of 3.4g / L;

[0168] Step 3: Material preparation

[0169] Under stirring, constant temperature of 65° C. and nitrogen protection, a nickel-containing metal salt solution (flow rate: 4% / h of the available volume of the reactor), a NaOH solution (flow rate: 1.4% / h to 1.5% / h of the available volume of the reactor) and ammonia water (flow rate: 0.08% / h to 0.16% / h of the available volume of the reactor) are simultaneously introduced into the reactor containing the bottom liquid; during the reaction process, the mother liquor is discharged through the concentration equipment, and the discharge rate of the mother liquor is consistent with the total liquid inlet rate;

[0170] During the reaction, the pH was adjusted to 11.00-11.20 within 4 hours of feeding by fine-tuning the flow rate of NaOH solution and ammonia water, and the ammonia concentration fluctuated within the range of 3-7 g / L, and the nickel concentration in the supernatant was changed and maintained within the range of 100-150 ppm, and finally a metal hydroxide reaction precipitation slurry with a diameter D50 of 14 μm was obtained. After washing, centrifuging, drying, and sieving to remove magnetism, the lithium-ion battery ternary positive electrode material precursor Ni 0.95 Co 0.03 Mn 0.015 Al 0.005 (OH)2.

[0171] Example 7 (Quaternary Precursor: Ni 0.95 Co 0.03 Mn 0.015 Zr 0.005 (OH)2:)

[0172] This embodiment provides a lithium ion battery positive electrode material precursor, and the preparation method thereof is as follows:

[0173] Step 1: Solution preparation

[0174] According to the molar ratio of nickel, cobalt, manganese and zirconium of 95:3:1.5:0.5, nickel sulfate, cobalt sulfate, manganese sulfate and zirconium sulfate crystals are weighed and calculated to prepare a nickel-containing metal salt solution with a total metal content of 2 mol / L.

[0175] Step 2: Primer Preparation

[0176] Pure water, NaOH solution (concentration 32wt%), and ammonia water (concentration 21wt%) were added into the reaction kettle, and stirred evenly at a constant temperature of 55°C to obtain a base solution with a pH of 11.40 and an ammonia concentration of 3.4g / L;

[0177] Step 3: Material preparation

[0178] Under stirring, constant temperature of 55° C. and nitrogen protection, a nickel-containing metal salt solution (flow rate: 4% / h of the available volume of the reactor), a NaOH solution (flow rate: 1.4% / h to 1.5% / h of the available volume of the reactor) and ammonia water (flow rate: 0.08% / h to 0.16% / h of the available volume of the reactor) are simultaneously introduced into a reactor containing a bottom liquid; during the reaction process, the mother liquor is discharged through a concentration device, and the discharge rate of the mother liquor is consistent with the total liquid inlet rate;

[0179] During the reaction, the pH was adjusted to 11.00-11.20 within 4 hours of feeding by fine-tuning the flow rate of NaOH solution and ammonia water, and the ammonia concentration fluctuated within the range of 3-7 g / L, and the nickel concentration in the supernatant was changed and maintained within the range of 250-300 ppm, and finally a metal hydroxide reaction precipitation slurry with a diameter D50 of 14 μm was obtained. After washing, centrifuging, drying, and sieving to remove magnetism, the reaction precipitation slurry was obtained as a precursor of the lithium-ion battery ternary positive electrode material Ni 0.95 Co 0.03 Mn 0.015 Zr 0.005 (OH)2.

[0180] Comparative Example 1 (Ternary Precursor: Ni 0.95 Co 0.04 Mn 0.01 (OH)2)

[0181] This comparative example provides a lithium ion battery positive electrode material precursor, and its preparation method is as follows:

[0182] Step 1: Solution preparation

[0183] According to the metal molar ratio of nickel, cobalt and manganese of 95:4:1, nickel sulfate, cobalt sulfate and manganese sulfate crystals were weighed and calculated to prepare a nickel-containing metal salt solution with a total metal content of 2 mol / L.

[0184] Step 2: Primer Preparation

[0185] Pure water, NaOH solution (concentration 32wt%), and ammonia water (concentration 21wt%) were added into the reaction kettle, and stirred evenly at a constant temperature of 65°C to obtain a base solution with a pH of 12.25 and an ammonia concentration of 6g / L;

[0186] Step 3: Material preparation

[0187] Under stirring, constant temperature of 65° C. and nitrogen protection, a nickel-containing metal salt solution (flow rate: 4% / h of the available volume of the reactor), a NaOH solution (flow rate: 1.4% / h to 1.5% / h of the available volume of the reactor) and ammonia water (flow rate: 0.08% / h to 0.16% / h of the available volume of the reactor) are simultaneously introduced into the reactor containing the bottom liquid; during the reaction process, the mother liquor is discharged through the concentration equipment, and the discharge rate of the mother liquor is consistent with the total liquid inlet rate;

[0188] During the reaction, the pH was adjusted to 11.60-11.80 within 4 hours of feeding by fine-tuning the flow rate of NaOH solution and ammonia water, and the ammonia concentration fluctuated within the range of 5-8 g / L, and the nickel concentration in the supernatant was changed and maintained within the range of ≤10 ppm, and finally a metal hydroxide reaction precipitation slurry with a diameter D50 of 14 μm was obtained. After washing, centrifuging, drying, and sieving to remove magnetism, the reaction precipitation slurry was obtained as a precursor of the lithium-ion battery ternary positive electrode material Ni 0.95 Co 0.04 Mn 0.01 (OH)2.

[0189] The obtained lithium-ion battery ternary cathode material precursor Ni 0.95 Co 0.04 Mn 0.01 The local SEM photo of the secondary particles of (OH)2 is as follows Fig.14 Its XRD spectrum is shown in Fig.15 shown.

[0190] Comparative Example 2 (Ternary Precursor: Ni 0.95 Co 0.04 Mn 0.01 (OH)2)

[0191] This comparative example provides a lithium ion battery positive electrode material precursor, and its preparation method is as follows:

[0192] Step 1: Solution preparation

[0193] According to the metal molar ratio of nickel, cobalt and manganese of 95:4:1, nickel sulfate, cobalt sulfate and manganese sulfate crystals were weighed and calculated to prepare a nickel-containing metal salt solution with a total metal content of 2 mol / L.

[0194] Step 2: Primer Preparation

[0195] Pure water, NaOH solution (concentration 32wt%), and ammonia water (concentration 21wt%) were added into the reaction kettle, and stirred evenly at a constant temperature of 65°C to obtain a base solution with a pH of 12.15 and an ammonia concentration fluctuating within a range of 5g / L;

[0196] Step 3: Material preparation

[0197] Under stirring, constant temperature of 65° C. and nitrogen protection, a nickel-containing metal salt solution (flow rate: 4% / h of the available volume of the reactor), a NaOH solution (flow rate: 1.4% / h to 1.5% / h of the available volume of the reactor) and ammonia water (flow rate: 0.08% / h to 0.16% / h of the available volume of the reactor) are simultaneously introduced into the reactor containing the bottom liquid; during the reaction process, the mother liquor is discharged through the concentration equipment, and the discharge rate of the mother liquor is consistent with the total liquid inlet rate;

[0198] During the reaction, the pH was adjusted to 9.30-9.50 within 4 hours of feeding by fine-tuning the flow rate of NaOH solution and ammonia water, and the ammonia concentration fluctuated within the range of 5-8 g / L, and the nickel concentration in the supernatant was changed and maintained within the range of 400-500 ppm, and finally a metal hydroxide reaction precipitation slurry with a diameter D50 of 14 μm was obtained. After washing, centrifuging, drying, and sieving to remove magnetism, the lithium-ion battery ternary positive electrode material precursor Ni 0.95 Co 0.04 Mn 0.01 (OH)2.

[0199] The obtained lithium-ion battery ternary cathode material precursor Ni 0.95 Co 0.04 Mn 0.01 The local SEM photo of the secondary particles of (OH)2 is as follows Fig.16 Its XRD spectrum is shown in Fig.17 shown.

[0200] The measured data and related parameters in the local SEM photos of the secondary particles of the precursor obtained in Examples 1-7 and Comparative Examples 1-2 are shown in Tables 1, 2 and 3 below:

[0201] Table 1 Preferred parameters for at least 60% of primary particles in the precursor

[0202]

[0203] Table 2 Fracture parameters of preferably at least 20% of the primary particles in the precursor

[0204]

[0205] Table 3 Precursor parameters

[0206]

[0207]

[0208] Weigh 2000 g of the precursors prepared in Example 1-7 and Comparative Example 1-2 and LiOH·H2O in a molar ratio of 1:1.03 respectively, mix them evenly with a high-speed mixer, and sinter them in a box furnace under air atmosphere at a sintering temperature of 780°C for 12 h. After cooling to room temperature, crush and sieve to obtain a positive electrode material.

[0209] The electrochemical performance test was conducted using a button-type semi-battery: the above-mentioned positive electrode material, conductive carbon black, and binder PVDF (polyvinylidene fluoride) were mixed into a slurry at a ratio of 8:1:1, and coated on aluminum foil to make a positive electrode sheet. The negative electrode sheet used a metal lithium sheet, and the electrolyte used 1 mol / L LiPF6 / EC:DMC (volume ratio 1:1). The battery shell, positive and negative electrode sheets, diaphragms, springs, and gaskets were assembled into a button-type battery in a vacuum glove box. The electrochemical performance test was conducted using a blue electric test system.

[0210] The test results are shown in Table 4:

[0211] Table 4 Electrochemical test results

[0212]

[0213] As can be seen from Table 4, the precursors prepared in Comparative Examples 1 and 2 do not have the high regularity and integrity of the precursors in this application, and the edges of the monolithic layers constituting the primary particles are uneven and more easily broken, and it is impossible to take into account the capacity, rate performance and cycle performance at the same time. The samples of Examples 1-3 have a capacity and rate performance close to those of Comparative Examples 1-2, and their cycle performance is significantly better than that of Comparative Examples 1 and 2; this performance advantage is due to the fact that the regularity and integrity of the primary particles are further optimized on the basis of a similar optimal porous and radially growing structure, and the XRD half-peak width is greatly narrowed, so that the overall crystal defects of the secondary particles are reduced and the crystallinity is further improved, thereby reducing the occurrence of side reactions and improving the cycle performance.

[0214] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

[0215] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.

Claims

1. A lithium-ion battery positive electrode material precursor, characterized in that: One of the precursor secondary particles includes N primary particles, and one of the primary particles includes N neatly stacked monolayers, and the edges of the monolayers are flat; Wherein, N is a positive integer and N≥2; The precursor has a half-peak width FWHM (001) of the (001) crystal plane corresponding to a diffraction angle of 2θ = 19.2 ± 1° and a half-peak width FWHM (101) of the (101) crystal plane corresponding to a diffraction angle of 2θ = 38.5 ± 1°, both of which are less than 0.550°; In one of the precursor secondary particles, at least 20% of the primary particles meet requirement ③: The monolithic layer includes a broken monolithic layer and / or an unbroken monolithic layer, and the broken monolithic layer is in a straight line or a bent shape; When the broken single layer is bent, the minimum angle γ between the extension line of the straight part and the bent part is less than or equal to 30 o ; In one of the precursor secondary particles, at least 20% of the primary particles meet at least one of the following requirements: Requirement ④: In one of the primary particles, the monolithic layers include broken monolithic layers and / or unbroken monolithic layers, and the number of fractures of each of the broken monolithic layers is less than or equal to 2; Requirement ⑤: In one of the primary particles, the monolithic layers include broken monolithic layers and / or unbroken monolithic layers, and the length of the longest fragment in each of the broken monolithic layers accounts for no less than 50% of the total length of the monolithic layer in which it is located; Requirement ⑥: In one of the primary particles, the monolayers include broken monolayers and / or unbroken monolayers, and the sum of the total length of all the unbroken monolayers and the total length of the longest fragments of all the broken monolayers accounts for no less than 60% of the total length of all the monolayers; The precursor chemical formula is Ni x M 1-x (OH)2, wherein 0.6≤x<1, and M is at least one of Co, Mn, Al, Fe, Ti, Zr, Mo, Cr, W, B, Mg, Ba, Nb and Sr.

2. The lithium-ion battery positive electrode material precursor according to claim 1, characterized in that: In one of the precursor secondary particles, at least 60% of the primary particles meet requirement ①: the length of the primary particle is not less than 200 nm, the width of the primary particle is not less than 50 nm, and the aspect ratio of the primary particle is not less than 1.

2.

3. The lithium-ion battery positive electrode material precursor according to claim 2, characterized in that: In one of the precursor secondary particles, at least 70% of the primary particles meet requirement ②: the length of the primary particle is 200-3000nm, the width of the primary particle is 50-300nm, and the aspect ratio of the primary particle is not less than 1.

2.

4. The lithium-ion battery positive electrode material precursor according to any one of claims 1 to 3, characterized in that: At least one of the following conditions is met: A. The precursor particle size D50 is 4-20 μm; C. The precursor has a BET specific surface area of ​​3-20 m 2 / g.

5. A method for preparing a lithium-ion battery positive electrode material precursor according to any one of claims 1 to 4, characterized in that: include: The raw materials including nickel metal salt solution, precipitant and complexing agent are introduced into the bottom liquid for reaction, and the pH value is controlled to be 9.8-11.3, the ammonia concentration is 2-12 g / L, and the nickel concentration in the supernatant is 70-350 ppm during the reaction; after the reaction, the solid-liquid separation, drying, sieving and demagnetization are performed to obtain the positive electrode material precursor of the lithium ion battery; The nickel-containing metal salt solution contains nickel and at least one of Co and Mn, or the nickel-containing metal salt solution contains only Ni; the raw materials introduced into the bottom liquid also include non-essential doped metal salt solution, and the doped metal in the doped metal salt solution includes at least one of Al, Fe, Ti, Zr, Mo, Cr, W, B, Mg, Ba, Nb and Sr; the bottom liquid includes sodium hydroxide solution, ammonia water and water; the flow rate of the nickel-containing metal salt solution is 2-10% / h of the available volume of the reactor, the flow rate of the precipitant is 0.5-3.5% / h of the available volume of the reactor, and the flow rate of the complexing agent is 0.01-1% / h of the available volume of the reactor; the mother liquor is discharged during the reaction, and the total liquid inlet rate is the sum of the flow rates of the raw materials introduced into the bottom liquid at the same time, and the discharge rate of the mother liquor is consistent with the total liquid inlet rate.

6. The preparation method according to claim 5, characterized in that: Satisfies at least one of the following conditions: d. the precipitant comprises sodium hydroxide solution, and the complexing agent comprises aqueous ammonia; g. The pH of the base solution is 10.5-12.3, and the ammonia concentration of the base solution is 3.4-6 g / L.

7. A positive electrode material for a lithium ion battery, characterized in that: The raw material comprises the lithium ion battery positive electrode material precursor according to any one of claims 1 to 4.

8. A lithium ion battery, characterized in that: The lithium-ion battery positive electrode material comprises the positive electrode material of claim 7.

9. An electrical equipment, characterized in that: Comprising the lithium ion battery as claimed in claim 8.

Citation Information

Patent Citations

  • Nickel-containing hydroxide precursor, preparation method thereof and positive electrode material

    CN112978813A

Cited By

  • Lithium-ion battery positive electrode material precursor and preparation method therefor, lithium-ion battery positive electrode material, lithium-ion battery and electric device

    EP4691996A1